Stakeholder perspectives on the clinical placement appraisal process in undergraduate nurse education: A qualitative study. Issue 4 (August 2022) - Cross, Rachel; Mosley, Ian, T.; Newton, Michelle; Edvardsson, David; Miller, Charne
Summary of Relevance: Problem or Issue: Little is known about the experience of formative and summative appraisals upon student learning in undergraduate nursing clinical placements. What is Already Known: Student learning in clinical placements is complex. Formative and summative appraisals contribute to student learning, but they require students and assessors to appraise student performance. What this Paper Adds: Evidence from key stakeholders for how three external factors; model of support offered, the assessment tool and role expectations, influenced the appraisal assessment and student learning in clinical placement. It provides an understanding of how the formative and summative appraisals are used into professional nursing registration. ABSTRACT: Background: Clinical placements are integral components of undergraduate nurse education. Assessment of student performance routinely involves formative and summative appraisals. Understanding how appraisals are used to promote student learning in undergraduate nurse education and into professional nursing registration is important. Aim: To describe the experience of clinical appraisal on student learning during clinical placements through the lens of the undergraduate nursing student, the clinical assessor, and university academic staff. Methods: Descriptive-exploratory-qualitative study using semi-structured interviews with eight undergraduate nursing students, three health service clinical nurses and six university staff were performed. Data were analysed using NVivo. Qualitative content analysis was performed. Results: Two categories emerged: continuum of learning; and assessment versus learning. Participants reported the formative and summative appraisals promoted student learning and development within the clinical placement and on their journey becoming nurses. The experience of the appraisal process was influenced by the tension between assessment and learning. Factors influencing the experience of the appraisal process for student learning included: the assessment tool, the clinical support model, and expectations of student and assessor role. Conclusion: Clinical placements are integral to a student's continuum of learning into professional registration. To facilitate positive learning experiences, orientation programs prior to the commencement of clinical placements for assessors and undergraduate students, could be included. Formal training in assessment and feedback may also be beneficial for clinical assessors. Clear expectations for models of clinical support and the process for appraisal assessment, may facilitate a more positive learning experience to promote better student outcomes.